Age-related differences in rejection rates, infections, and tacrolimus exposure in pediatric kidney transplant recipients in the CERTAIN registry - Baghai Arassi, Maral; Feißt, Manuel; Krupka, Kai; Awan, Atif; Benetti, Elisa; Düzova, Ali; Guzzo, Isabella; Kim, Jon Jin; Kranz, Birgitta; Litwin, Mieczysław; Oh, Jun; Büscher, Anja; et al. (Kidney international. Reports, 2024)
Introduction - Data on age-related differences in rejection rates, infectious episodes, and tacrolimus exposure in pediatric kidney transplant recipients (pKTRs) on a tacrolimus-based immunosuppressive regimen are scarce. - Methods - We performed a large-scale analysis of 802 pKTRs from the Cooperative European Paediatric Renal Transplant Initiative (CERTAIN) registry from 40 centers in 14 countries. The inclusion criteria were a tacrolimus-based immunosuppressive regimen and at least 2 years of follow-up. The patient population was divided into 3 age groups (infants and young children aged <6 years, school-aged children 6-12 years, and adolescents aged >12 years) to assess age-related differences in outcome. - Results - Median follow-up was 48 months (interquartile range [IQR], 36-72). Within the first 2 years posttransplant, infants, and young children had a significantly higher incidence of infections (80.6% vs. 55.0% in adolescents, P < 0.001) and a significantly higher number of cumulative hospital days (median 13 days vs. 7 days in adolescents, P < 0.001). Adolescents had a significantly higher rate of biopsy-proven acute rejection episodes in the first-year posttransplant (21.7%) than infants and young children (12.6%, P = 0.007). Infants and young children had significantly lower tacrolimus trough levels, lower tacrolimus concentration-to-dose (C/D) ratios as an approximation for higher tacrolimus clearance, and higher tacrolimus interpatient variability (TacIPV) (all P < 0.01) than adolescents. - Conclusion - This is the largest study to date in European pKTRs on a tacrolimus-based immunosuppressive regimen, and it shows important age-related differences in rejection rates, infection episodes, as well as tacrolimus exposure and clearance. This data suggests that immunosuppressive therapy in pKTRs should be tailored and personalized according to the age-specific risk profiles of this heterogeneous patient population. The data may serve as a benchmark for future studies with novel immunosuppressive drugs.
Online veröffentlicht: 2. September 2024
Gesehen am 10.09.2025